Pengaruh Service Quality dan Keragaman Produk Terhadap Kepuasan Konsumen - Kariani, Ni Wayan Yanik; Kawiana, I Gede Putu; Wilyadewi, Ida I Dewa Ayu Yayati (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Customer satisfaction is influenced by many factors such as service quality and product diversity. This study aims to understand the effect of service quality and product diversity on customer satisfaction of Optik Mitra Mandiri. The research method used is quantitative. Research location at Optik Mitra Mandiri. The sample used was 100 respondents. The data analysis techniques used are Validity Test, Reliability, Classical Assumptions, Multiple Linear Regression, Coefficient of Determination, t Test and F Test. Based on the results of the study, it was found that service quality has a significant positive effect on consumer satisfaction, product diversity has a significant positive effect on consumer satisfaction, and simultaneously service quality and product diversity have a positive and significant effect on consumer satisfaction. The magnitude of the influence of the independent variable on consumer satisfaction was 59.9%. The suggestion in this study is that Optik Mitra Mandiri should add facilities that are still lacking, always maintain store cleanliness so that later make consumers comfortable when visiting, increase product variety and increase employee alacrity and speed in providing services.